An investigation of the enzymatic cleavage of κ-casein in non-coagulating milk. (October 2020) - Nilsson, Kajsa; Abdelghani, Ahmed; Burleigh, Stephen; Buhelt Johansen, Lene; Lindmark-Månsson, Helena; Paulsson, Marie; Glantz, Maria
Abstract: Non-coagulating milk is unwanted in cheese production because it impairs chymosin-induced coagulation properties in bulk milk. Milk samples were analysed to investigate the coagulation process in non-coagulating milk for comparison with milk samples that have a high coagulation ability. This was done by measuring two peptides after chymosin cleavage, namely para-κ-casein and caseinomacropeptide, in all the milk samples using capillary electrophoresis. The results showed that cleavage of κ-casein into para-κ-casein and caseinomacropeptide occurred in both coagulation groups, suggesting that the aggregation stage is the cause of non-coagulating milk. Non-coagulating milk had lower content of para-κ-casein after chymosin addition compared with coagulating milk, which might be the result of a lower content of available κ-casein. Furthermore, this study indicates that there are different mechanisms that explain good coagulation ability and lack of coagulation ability of milk. The results can be useful in understanding the potential chemical mechanisms behind non-coagulating milk.